Determination of contract base payments to feeder-pig producers - Parcell, J.L.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Risks associated with independent feeder-pig production have prompted producers to seek alternative production and marketing methods. A means of reducing risk has developed through contract feeder-pig producing. Research results indicate that slightly risk-averse producers required contract base payments ranging from $7.50 to $28.50 per head. Strongly risk-averse producers required contract base payments ranging from $2.50 to $17.75 per head. The lower end of the ranges is for a low-profit producer. The upper end of the ranges is for a high-profit producer.
Keywords: Swine; Risk management; Contract feeder-pig production